The Effect of Training, Competence and Motivation on Organizational Commitment Through Job Satisfaction as a Mediation Variable in the Directorate of the Air Police - Rio Dwi Hariono; Yohny Anwar; Darmilisani Darmilisani (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the influence of training, competence, and motivation on organizational commitment through job satisfaction as a mediating variable in the pilot of the Air Police Directorate. The study used a causal associative quantitative approach with a total population of 179 active pilots. The determination of the sample using the Slovin formula with an error rate of 5% resulted in 123 respondents who were selected through simple random sampling. Primary data was collected through a Google Form electronic questionnaire with a Likert scale of 1-5, and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS software. The results showed that training and motivation had a significant positive effect on organizational commitment with a path coefficient of 0.427 and 0.410, respectively, and on job satisfaction with a coefficient of 0.596 and 0.382, with training being the strongest predictor of job satisfaction. On the other hand, competence does not have a significant effect on both organizational commitment and job satisfaction, and job satisfaction also does not have a significant effect on organizational commitment. The results of the mediation test showed that job satisfaction was unable to mediate the influence of the three independent variables on organizational commitment, indicating that in police institutions, organizational commitment is built through different mechanisms, namely structural ties, corps values, and dedication to state service, not through job satisfaction.